Counseling on the Use of Semantic Scholar in Improving Digital Literacy of Students in Indonesia: Penelitian - Andry Nurmansyah; Ria Kristia Fatmasari; Tobari; Adi Artino; Tania Dwika Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The author conducted this socialization towards students and junior lecturers. This socialization was conducted during the author's teaching hours and informal discussions among colleagues in the office. The result in this article show the author conducted lasted for approximately four meetings with students at the author's teaching place with the concept of socializing the use of Perpexity AI once and directly practicing writing journals and thesis frameworks with three evaluations. When conducting socialization, the author explained a number of advantages of Perplexity AI, including: 1. More Optimal Search Engine Capabilities: Google Search is more optimal in searching using keywords. If we enter a long sentence, Google often cannot find search results. This is different from Perplexity AI which is able to understand the context of the writing we input, whether it is in the form of long text or just keywords. Anyone who uses it will certainly be facilitated. 2. More Accurate Answers: Although ChatGPT has a broad understanding of language, they may not always understand the context in depth. This causes answers that are less precise or not in accordance with what the user means. Unlike Perplexity which has a better understanding of context so that its answers can be more relevant and accurate. 3. Chatbot with Advanced Capabilities: This AI can respond to any conversation you make, even if it's just a